ASSESSING NURSES` KNOWLEDGE OF SAFE BLOOD TRANSFUSION PRACTICES IN A TERTIARY CARE HOSPITAL IN PESHAWAR PAKISTAN: A CROSS-SECTIONAL STUDY (The Research of Medical Science Review, 2025)
Introduction: Blood transfusion is a critical medical procedure used to replace lost components of the blood, such as red blood cells, plasma, or platelets, in patients with conditions like anemia, trauma, or surgical blood loss. Ensuring safe transfusion practices is vital to prevent complications, including transfusion reactions and infections. Nurses play a key role in this process, requiring comprehensive knowledge and skills to maintain patient safety and improve outcomes. Methodology: A descriptive cross-sectional study was conducted in a tertiary care hospital in Peshawar, Pakistan, to assess nurses' knowledge of safe blood transfusion practices. A total of 152 registered nurses from ICU, surgical units, emergency, and medical wards were selected via convenience sampling. Nurses with at least six months of transfusion-related experience were included. Data were collected using a pre-tested, structured questionnaire covering demographics, knowledge, and safety practices. Statistical analysis was performed using SPSS v25, with a p-value <0.05 considered significant. Ethical approval and informed consent were obtained. Result: This study assessed the knowledge of 152 nurses on safe blood transfusion practices at a tertiary care hospital in Peshawar. The highest knowledge score was on transfusion indications (75.7%), while the lowest was on patient involvement (62.5%). Nurses with 16+ years of experience had significantly higher knowledge scores (p = 0.041). Gender and department showed no significant differences (p > 0.05). Gaps in recognizing transfusion reactions and patient involvement highlight the need for targeted educational interventions to improve transfusion safety practices. Conclusion: The study revealed that while 75.7% of nurses were knowledgeable about blood transfusion indications, there were notable gaps in understanding transfusion reactions and involving patients in the process. Although post-intervention knowledge scores improved significantly, indicating the effectiveness of educational programs, overall knowledge and practices still need enhancement. Continuous professional development, regular training, and practical workshops are essential to bridge these gaps, promote safe transfusion practices, and ensure patient safety in healthcare settings.